Conservative Surgical Management of Late Carotid Patch Infection in a Patient with Subsequent Stenting for Restenosis. (January 2022) - Torres-Blanco, Álvaro; Altable-García, Mario; Miralles-Hernández, Manuel
Carotid patch infection is a rare but dreaded complication after endarterectomy. About 160 cases can be found in literature, but presentation in a patient with post-endarterectomy stenting has not been reported. Most frequent clinical manifestations include the occurrence of a sinus, a pseudoaneurysm, or neck swelling, but in severe cases it may present anastomosis dehiscence with hematoma or hemorrhage. Usually, patch removal and reconstruction is recommended, but there is not a standard protocol for management. Conservative surgical management with patch preservation has only been reported in a minority of cases. We report a patient with a history of carotid endarterectomy and subsequent carotid stenting 21 months later because of >80% restenosis. He presented a sinus in the scar 81 months after the former intervention. The patient underwent surgery, and during the procedure, a detachment of a small segment of the Dacron patch from the surrounding tissue was found. The sinus tract was resected, and after verifying the integrity of the patch, it was irrigated with rifampicin and preserved in situ. S. epidermidis was isolated from tissue cultures. Twenty-four months later, the patient remains asymptomatic and duplex ultrasound shows no signs of infection. Conservative surgical approach can be a valid option for treatment and may be considered in selected patients with limited infection.